Biomimetic on-chip assay reveals the anti-metastatic potential of a novel thienopyrimidine compound in triple-negative breast cancer cell lines - Sigdel, Indira; Ofori-Kwafo, Awurama; Heizelman, Robert J.; Nestor-Kalinoski, Andrea; Prabhakarpandian, Balabhaskar; Tiwari, Amit K.; Tang, Yuan (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: This study presents a microfluidic tumor microenvironment (TME) model for evaluating the anti-metastatic efficacy of a novel thienopyrimidines analog with anti-cancer properties utilizing an existing commercial platform. The microfluidic device consists of a tissue compartment flanked by vascular channels, allowing for the co-culture of multiple cell types and providing a wide range of culturing conditions in one device. Methods: Human metastatic, drug-resistant triple-negative breast cancer (TNBC) cells (SUM159PTX) and primary human umbilical vein endothelial cells (HUVEC) were used to model the TME. A dynamic perfusion scheme was employed to facilitate EC physiological function and lumen formation. Results: The measured permeability of the EC barrier was comparable to observed microvessels permeability in vivo. The TNBC cells formed a 3D tumor, and co-culture with HUVEC negatively impacted EC barrier integrity. The microfluidic TME was then used to model the intravenous route of drug delivery. Paclitaxel (PTX) and a novel non-apoptotic agent TPH104c were introduced via the vascular channels and successfully reached the TNBC tumor, resulting in both time and concentration-dependent tumor growth inhibition. PTX treatment significantly reduced EC barrier integrity, highlighting the adverse effects of PTX on vascular ECs. TPH104c preserved EC barrier integrity and prevented TNBC intravasation. Discussion: In conclusion, this study demonstrates the potential of microfluidics for studying complex biological processes in a controlled environment and evaluating the efficacy and toxicity of chemotherapeutic agents in more physiologically relevant conditions. This model can be a valuable tool for screening potential anticancer drugs and developing personalized cancer treatment strategies.